Dietary N-carbamylglutamate (NCG) supplementation improves the survival, digestive and immunological parameters by promoting ammonia excretion in Chinese mitten crab (Eriocheir sinensis), under ammonia nitrogen stress - Zhiqiang Liu; Aoya Shi; Mengjie Zhao; Chen Zheng; Jiayi Chen; Chao Niu; Yameng Song; Xueli Ma; Yangyang Pang; Xingliang Shi; Yongxu Cheng; Xiaozhen Yang (Aquaculture and Fisheries)
Ammonia nitrogen is one of the most common environmental stress factors in aquaculture. The aim of this experiment was to evaluate the effects of ammonia nitrogen stress on ammonia metabolism, digestion and immune function as well as the protective effects of dietary N-carbamylglutamate (NCG) in the Chinese mitten crab (Eriocheir sinensis). Two feeds were used, namely a control feed (regular commercial feed) and an NCG feed (NCG (302.96 ± 4.07) mg/kg added). Subsequently, animals fed by these two feeds were exposed to 30 mg/L or 60 mg/L ammonia nitrogen stress (named A30 or A60) for 21 days, respectively. The rate of hemolymph ammonia excretion was significantly increased in NCG group compared to C (control) group (P < 0.05). Hemolymph ammonia levels were significantly lower in NCG A30 (NCG feed and A30) and NCG A60 (NCG feed and A60) groups compared to A30 (control feed and A30) and A60 (control feed and A60) groups (P < 0.05). Glutamate dehydrogenase and glutamine synthetase activities in the gills and hepatopancreas of NCG A60 group were significantly increased compared with the A60 group, which promoted glutamine synthesis (P < 0.05). The cumulative mortality rate of Eriocheir sinensis in NCG A30 and NCG A60 groups were effectively reduced (P < 0.05). The arginine levels of hepatopancreas were significantly increased in NCG A60 group (P < 0.05). Under ammonia nitrogen stress, NCG significantly increased the activities of trypsin, pepsin, lipase and α-Amylase in NCG feed group, and promoted feeding (P < 0.05). In hemolymph, hepatopancreas and intestine, NCG significantly increased nitric oxide synthase activity, lysozyme and phenol oxidase activities compared to the ammonia nitrogen stress group (P < 0.05). The results indicated that, NCG added in feed could decelerate the toxic effects of ammonia on Eriocheir sinensis by promoting ammonia excretion and accelerating glutamine and endogenous arginine synthesis by metabolism. Moreover, the activity of digestive enzymes and immune-related enzymes is improved.